Golgin A7 family member B (GOLGA7B) is a plausible novel gene associating high glycaemic index diet with acne vulgaris - Say, Yee How*; Yang, Yie Sio; Heng, Anna Hwee Sing; Ng, Yu Ting; Matta, Sri Anusha; Pang, Sze Lei; Teh, Keng Foo *; Wong, Yi Ru *; Shah, Smyrna Moti Rawanan; Kavita, Reginald * (Wiley, 2022)
While the IGF1/FoxO1/mTORC1 signalling pathway is a well-established nutrigenomic link between high glycaemic index (GI)/glycaemic load (GL) diet and acne vulgaris, other signalling pathways remain elusive. Therefore, we aimed to investigate other genes that are involved in the high GI/GL diet-acne link, using our Singapore/Malaysia population epidemiological, genomics and transcriptomics data. High GI/GL dietary habit of 3207 acne cases (1869 and 1341 further classified into severity and scarring grades, respectively) and 2521 controls were evaluated based on Quality of Diet based on Glycaemic Index Score (QDGIS). Overlapping concordant differentially expressed genes (DEGs) between acne case-controls and QDGIS poor-moderate/good classes were identified from whole-transcriptome sequencing data of PBMC of a subset of participants. Finally, we assessed the expression quantitative trait loci (eQTL) association of single nucleotide polymorphisms (SNPs) of the concordant DEGs. Daily intake of fruits significantly reduced the risk of acne presentation, severity and scarring by up to 48.5%. Those with good QDGIS had significantly lower risk of mild and moderate/severe acne, and grade 1/2 acne scarring. Sequential filtering identified four overlapping concordant DEGs that were significantly associated with acne and QDGIS, namely GOLGA7B, SNCB, LOC102723849 and LOC283683. Combining transcriptome and genetic association data, we identified intronic SNP rs1953947 in GOLGA7B as an eQTL for acne. In conclusion, we identified GOLGA7B as a plausible novel gene that links high GI/GL with acne, and hence propose a model for the involvement of Golga7b in high GI/GL diet-acne pathogenesis, which includes palmitoyl acyltransferase zDHHC5, fatty acid translocase CD36 and palmitic acid.